Changing emission of divalent samarium doped into barium octoborate as a function of firing time. Issue 2 (7th February 2019) - Yoo, Kyung W.; Drozdowski, Christopher H.; Gharavi-Naeini, Jafar; Stump, Nathan A.
Abstract: Barium octoborate has been synthesized by air firing of co-precipitated borates with additional boric acid. During the firing process, samarium ions doped into the matrix are reduced to the divalent state. Two different divalent samarium emission spectra have been observed from the material as a function of the firing history, even though the structure, as identified by powder X-ray diffraction remained consistent. A minor barium pentaborate impurity, in conjunction with significant thermal variability in the strength of the divalent samarium emission generated by the different sites in the two borate materials, appears to give rise to this phenomenon.